1993
DOI: 10.2214/ajr.161.4.8372744
|View full text |Cite
|
Sign up to set email alerts
|

Differences in CT density between dependent and nondependent portions of the lung: influence of lung volume.

Abstract: OBJECTIVE.Lung tissue, blood, and air determine the physical density of the lung and hence the attenuation measured on CT scans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(58 citation statements)
references
References 20 publications
5
47
0
6
Order By: Relevance
“…For instance, Verschakelen et al (22) found gradients in computed tomography (CT) lung density between dependent and nondependent lung regions that were most marked at low lung volumes, without, however, observing any difference in density gradients between supine and prone postures. Because the observed regional differences in CT lung densities were explained by gravity-dependent differences in perfusion and lung inflation, the similar pattern observed supine and prone would suggest either that perfusion and ventilation gradients between dependent and nondependent were similar prone and supine, or that both the perfusion and ventilation gradients are reduced in the prone vs. supine posture.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Verschakelen et al (22) found gradients in computed tomography (CT) lung density between dependent and nondependent lung regions that were most marked at low lung volumes, without, however, observing any difference in density gradients between supine and prone postures. Because the observed regional differences in CT lung densities were explained by gravity-dependent differences in perfusion and lung inflation, the similar pattern observed supine and prone would suggest either that perfusion and ventilation gradients between dependent and nondependent were similar prone and supine, or that both the perfusion and ventilation gradients are reduced in the prone vs. supine posture.…”
Section: Discussionmentioning
confidence: 99%
“…Another complication is that respiration occurs throughout the PET acquisition whereas a single phase of respiration (10) 23 (11) 17 (11) 13 (9) 12 (7) 13 (9) 17 (13) 23 (17) 31 (19) 40 (21) 50 (22) 13 (11) 10 (8)…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these errors are separate from those induced by assigning erroneous m-coefficients to the lungs and do not alter the conclusions of this study. On the contrary, without a means to account for the changing lung m-coefficients with respiration (16,17,19), optimal correction of the transmission to emission mismatch (via a time-varying m-map) would be flawed. The principal reason that this study was performed using a large-animal model was that it allowed for precise control of their ventilation; the lungs could be held at the same respiratory state during the CT and MR image acquisitions.…”
Section: (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…The characterization of the disease severity was mainly done by looking at different gray scaling densities interpreted as infiltrates, consolidation or atelectasis during the acute phase [15] and after the resolution of ARDS [23]. The measurement of lung and intrathoracic gas volumes by CT has been validated previously [24,25], but has not been used for as a routine procedure due to complicated and time-consuming exposure and analysis techniques. More recently, from the distribution of frequencies distributions it was attempted to describe changes within the lung induced by certain interventions [7] with regard to the distribution of ventilation.…”
Section: Discussionmentioning
confidence: 99%